Surface Functionalization of Gold Nanoparticles for Simultaneous Suppression of Cancer Stem Cells and Cancer Cells (Journal of Cancer Research Updates, 2014)
Surface functionalization of gold nanoparticles is designed for simultaneous suppression of cancer stem cells and cancer cells. The fundamental mechanism of the simultaneous suppression is based on the blocking against DNA polymerase, DNA helicase and RNA polymerase by positively charged gold nanoparticles introduced into nucleuses. In addition, applications of physical fields (ultrasound, X-ray or electromagnetic wave) will enhance the suppression effects of the cancer cells by interactions between gold nanoparticles and physical fields. It is predicted theoretically that the surface functionalization of gold nanoparticle is promising for radical treatments of cancers.